2019
DOI: 10.1038/s41408-019-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

CBFβ-MYH11 interferes with megakaryocyte differentiation via modulating a gene program that includes GATA2 and KLF1

Abstract: The inv(16) acute myeloid leukemia-associated CBFβ-MYH11 fusion is proposed to block normal myeloid differentiation, but whether this subtype of leukemia cells is poised for a unique cell lineage remains unclear. Here, we surveyed the functional consequences of CBFβ-MYH11 in primary inv(16) patient blasts, upon expression during hematopoietic differentiation in vitro and upon knockdown in cell lines by multi-omics profiling. Our results reveal that primary inv(16) AML cells share common … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…ERG knockdown reduced ME-1 colony formation in methylcellulose (Figure S8E), consistent with a shift away from the HSC-like state. We also analysed RNAseq data from GATA2 over-expression in ME-1 cells 63 and found that increased GATA2 led to increased TAL1 and RUNX1, and reduced ERG and LMO2, similar to expression changes between Ery-precursor-like and HSC-like ME-1 cells (Figure 5C, left, compare to Figure 4F, left). GSEA analysis was used to compare GATA2 driven changes in global gene expression to expression differences between Ery-precursors and HSCs.…”
Section: Direct Manipulation Of Gata2 and Erg Promotes Erythroid Traj...mentioning
confidence: 68%
“…ERG knockdown reduced ME-1 colony formation in methylcellulose (Figure S8E), consistent with a shift away from the HSC-like state. We also analysed RNAseq data from GATA2 over-expression in ME-1 cells 63 and found that increased GATA2 led to increased TAL1 and RUNX1, and reduced ERG and LMO2, similar to expression changes between Ery-precursor-like and HSC-like ME-1 cells (Figure 5C, left, compare to Figure 4F, left). GSEA analysis was used to compare GATA2 driven changes in global gene expression to expression differences between Ery-precursors and HSCs.…”
Section: Direct Manipulation Of Gata2 and Erg Promotes Erythroid Traj...mentioning
confidence: 68%
“…On the other hand, the aberrant activation of KLF1 and TAL1 may illustrate an oncogenic function of IRX1 in megakaryoblastic AML. The CBFb-MYH11 fusion gene reportedly deregulates the activity of GATA2 and KLF1, and thus inhibits megakaryopoiesis and erythropoiesis [ 63 ]. Here, while excluding the presence of CBFb-MYH11 fusion, we detected the aberrant activity of IRX3/IRX5, an alternative mechanism to perturb myeloid differentiation via KLF1 deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the bulk of ME-1 cells were assigned as HSC-like, we reasoned that increased expression of GATA2 might alter their trajectory towards the Ery-precursor-like state. We analysed RNAseq data from GATA2 over-expression in ME-1 cells 61 and found that increased GATA2 led to increased TAL1 and RUNX1, and reduced ERG and LMO2, similar to expression changes between Ery-precursor-like and HSC-like ME-1 cells( Figure 5C, left, compare to Figure 4F, left). GSEA analysis was used to compare GATA2 driven changes in global gene expression to expression differences between Ery-precursors and HSCs.…”
Section: Direct Manipulation Of Gata2 and Erg Promotes Erythroid Trajmentioning
confidence: 65%